Associations of breast milk adiponectin, leptin, insulin and ghrelin with maternal characteristics and early infant growth: a longitudinal study. Issue 12 (28th December 2018) - Yu, Xinting; Rong, Shi Song; Sun, Xiujing; Ding, Guofang; Wan, Weilin; Zou, Liying; Wu, Shaowen; Li, Ming; Wang, Danhua
Abstract: Breast milk (BM) hormones have been hypothesised as a nutritional link between maternal and infant metabolic health. This study aimed to evaluate hormone concentrations in BM of women with and without gestational diabetes mellitus (GDM), and the relationship between maternal factors, BM hormones and infant growth. We studied ninety-six nulliparous women with ( n 48) and without GDM and their exclusively breastfed term singletons. Women with GDM received dietary therapy or insulin injection for euglycaemia during pregnancy. Hormone concentrations in BM, maternal BMI and infant growth were longitudinally evaluated on postnatal days 3, 42 and 90. Mothers with GDM had decreased concentrations of adiponectin ( P colostrum <0·001; P mature-milk =0·009) and ghrelin ( P colostrum =0·011; P mature-milk <0·001) and increased concentration of insulin in BM ( P colostrum =0·047; P mature-milk =0·021). Maternal BMI was positively associated with adiponectin ( β =0·06; 95 % CI 0·02, 0·1; P =0·001), leptin ( β =0·16; 95 % CI 0·12, 0·2; P <0·001) and insulin concentrations ( β =0·06; 95 % CI 0·02, 0·1; P <0·001), and inversely associated with ghrelin concentration in BM ( β =–0·08; 95 % CI –0·1, –0·06; P <0·001). Among the four hormones, adiponectin was inversely associated with infant growth in both the GDM ( β weight-for-height =–2·49; 95 % CI –3·83, –1·15; P <0·001; β head-circumference =–0·39; 95 % CI –0·65, –0·13; P =0·003) and healthy groups ( β weight-for-height =–1·42; 95 % CI –2·38, –0·46; P =0·003; β head-circumference =–0·15; 95 % CI –0·27, –0·03; P =0·007). Maternal BMI and GDM are important determinants of BM hormone concentrations. Milk-borne adiponectin is determined by maternal metabolic status and plays an independent down-regulating role in early infant growth.